Biogenic synthesis, characterization, and evaluation of synthesized nanoparticles against the pathogenic fungus Alternaria solani - Narware, Jeetu; Singh, Satyendra P.; Manzar, Nazia; Kashyap, Abhijeet Shankar (Frontiers in Microbiology, 2023)
In the present study, Trichoderma harzianum culture filtrate (CF) was used as a reducing and capping agent to synthesize silver nanoparticles (Ag NPs) in a quick, simple, cost-effective, and eco-friendly manner. The effects of different ratios (silver nitrate (AgNO3): CF), pH, and incubation time on the synthesis of Ag NPs were also examined. Ultraviolet–visible (UV–Vis) spectra of the synthesized Ag NPs showed a distinct surface plasmon resonance (SPR) peak at 420 nm. Spherical and monodisperse NPs were observed using scanning electron microscopy (SEM). Elemental silver (Ag) was identified in the Ag area peak indicated by energy dispersive x-ray (EDX) spectroscopy. The crystallinity of Ag NPs was confirmed by x-ray diffraction (XRD), and Fourier transform infrared (FTIR) was used to examine the functional groups present in the CF. Dynamic light scattering (DLS) revealed an average size (43.68 nm), which was reported to be stable for 4 months. Atomic force microscopy (AFM) was used to confirm surface morphology. We also investigated the in vitro antifungal efficacy of biosynthesized Ag NPs against Alternaria solani, which demonstrated a significant inhibitory effect on mycelial growth and spore germination. Additionally, microscopic investigation revealed that Ag NP-treated mycelia exhibited defects and collapsed. Apart from this investigation, Ag NPs were also tested in an epiphytic environment against A. solani. Ag NPs were found to be capable of managing early blight disease based on field trial findings. The maximum percentage of early blight disease inhibition by NPs was observed at 40 parts per million (ppm) (60.27%), followed by 20 ppm (58.68%), whereas in the case of the fungicide mancozeb (1,000 ppm), the inhibition was recorded at 61.54%.